The Olympic Biathlon – Recent Advances and Perspectives After Pyeongchang - Laaksonen, Marko S.; Jonsson, Malin; Holmberg, Hans-Christer (Frontiers in Physiology, 2018)
The biathlon, combining cross-country ski skating with rifle marksmanship, has been an Olympic event since the Winter Games in Squaw Valley, USA, in 1960. As a consequence of replacing the classical with the skating technique in the 1980’s, as well as considerable improvements in equipment and preparation of ski tracks and more effective training, the average biathlon skiing speed has increased substantially. Moreover, the mass-start, pursuit and sprint races have been introduced. Indeed, two of the four current individual Olympic biathlon competitions involve mass-starts, where tactics play a major role and the outcome is often decided during the last round of shooting or final sprint. Biathlon is a demanding endurance sport requiring extensive aerobic capacity. The wide range of speeds and slopes involved requires biathletes to alternate continuously between and adapt different skating sub-techniques during races, a technical complexity that places a premium on efficiency. Although the relative amounts of endurance training at different levels of intensity have remained essentially constant during recent decades, today’s biathletes perform more specific endurance training on roller skis on terrain similar to that used for competition, with more focus on the upper-body, systematic strength and power training and skiing at higher speeds. Success in the biathlon also requires accurate and rapid shooting while simultaneously recovering from high-intensity skiing. Many different factors, including body sway and triggering behaviour and even psychology, influence shooting performance. Thus, the complexity of biathlon deserves greater research focus on areas such as, e.g., race tactics, skating techniques or shooting process.